(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Anthropology plays an important role in various medicolegal aspects; apart from determination of Age, Sex and Race of individual, stature is also one of the important parameter of identification various civil and criminal cases. Therefore efforts have been made to determine association between stature and length of clavicle if any. Materials and Method: The present research was carried out in department of Anatomy JNMC Sawangi (M) Wardha; was conducted on total 50 Female individual of age 17–24. The length was calculated with the help of osteometric callipers for clavicles from anatomical landmarks and stature was calculated in centimetres. Conclusion. From present research it was concluded that the length of clavicle and stature reveals positive correlation and the linear relationship between the living stature and length of clavicle of each side was carried out in the form of regression equation.